ANALYSIS OF THE IMPLEMENTATION OF MSME DIGITAL TRANSFORMATION IN THE 3T REGION: A CASE STUDY ON THE PROGRAM OF THE COOPERATIVES, MSMES, INDUSTRY, AND TRADE OFFICE OF PUNCAK JAYA REGENCY, CENTRAL PAPUA - Hendrik Ibo; Fedianty Augustinah; Aris Sunarya (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study investigates the implementation of digital transformation programs for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s 3T regions (Frontier, Outermost, and Disadvantaged), focusing specifically on Puncak Jaya Regency in Central Papua. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The study aims to explore how local governments implement digitalization strategies for MSMEs in remote areas with limited infrastructure and technological access. Findings indicate that approximately 30–40% of MSMEs began adopting simple digital tools such as social media platforms for product promotion and mobile cashier applications for recording transactions. These changes were largely influenced by training and mentoring programs initiated by the local Department of Cooperatives and SMEs. Despite these advancements, several challenges remain, including poor internet connectivity, low digital literacy, lack of continuous technical assistance, and limited availability of digital devices. To address these obstacles, the local government applied adaptive strategies such as delivering training in local languages, providing hands-on support, and conducting outreach directly to the business owners in their communities. While early economic impacts are modest—such as slight increases in weekly revenue and broader customer reach—there is potential for long-term growth. The study concludes that a sustainable, community-based, and culturally appropriate model of digital transformation is essential to ensure inclusive development for MSMEs in Indonesia’s remote and underserved areas like Puncak Jaya.